COMPARISON BETWEEN THE PATTERN OF UNNATURAL DEATH AMONG FEMALES IN THE REPRODUCTIVE AGE GROUP AND WOMEN AGED 50 YEARS AND ABOVE BROUGHT FOR MEDICO-LEGAL AUTOPSY (Journal of Forensic Medicine & Toxicology, 2022)
Background: As per a survey conducted by UK-based Thompson Reuters Foundation, India was the 4th most dangerous country for females globally with which the threats ranging from domestic violence, foeticide, and other crimes leading to unnatural death in females. By knowing the cause of unnatural death among females in different age group would guide us to adopt preventive measures to minimize these types of death. Aim: To compare the unnatural deaths among females in the reproductive age group with females aged 50 years and above. Methodology: A retrospective record-based study, by analysing the records from the year Jan 2019 to Jan 2021 was conducted in the department of forensic medicine of Karur government medical college hospital. A total of 250 deaths were reported in that period and all these deaths were analysed retrospectively. The data were grouped into two groups one group were females in the reproductive age group (15 – 49 years) and the other group was females >49 years of age. Type and cause of death with the post mortem findings were recorded in the proforma. Results: Suicide was the most common type of death among the women in the reproductive age group and among women aged more than 49 years accident was found to be the most common type of death and this difference was found to be statistically significant (p
Keywords: Females; Unnatural Deaths; Suicide; Accidents; Reproductive Age Group; Autopsy